Nyāyasāra of Bhāsarvajña, a critical study - Narayanan, T. K. (Mittal Publications, 1992)
Study of the Nyāyasāra, aphoristic work on Hindu logic and epistemology by Bhāsarvajña, 10th century Kashmiri scholar.